2011
DOI: 10.2807/ese.16.35.19959-en
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing large mumps outbreak in the Federation of Bosnia and Herzegovina, Bosnia and Herzegovina, December 2010 to July 2011

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Most patients with measles were not vaccinated or had an unknown vaccination status. Gaps in the immunization program in the war (1992)(1993)(1994)(1995) and postwar period (1996)(1997)(1998) left many children susceptible to measles, rubella and mumps [4][5][6]. At the time of the current outbreak, the war generation had reached the age of 16 to 23 years, largely falling into the most affected age bracket.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients with measles were not vaccinated or had an unknown vaccination status. Gaps in the immunization program in the war (1992)(1993)(1994)(1995) and postwar period (1996)(1997)(1998) left many children susceptible to measles, rubella and mumps [4][5][6]. At the time of the current outbreak, the war generation had reached the age of 16 to 23 years, largely falling into the most affected age bracket.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009-2010 a rubella epidemic involved 1900 cases [4]. This was followed by an epidemic of mumps in 2010-2012 with 7895 reported cases [5,6] and a measles outbreak in 2014-2015. After the last measles outbreak in FB&H in 2007 caused by genotype D4 [7] until the beginning of 2014 (February) only sporadic cases of measles were reported (http://www.zzjzfbih.ba/page/6/?s=morbili).…”
Section: Introductionmentioning
confidence: 99%
“…For example, mumps outbreaks in the Balkans were reported in 2011 due to an interruption in vaccination programs in the 1990s 26 . Over a decade later, mumps-related cases mostly involved non-immunized children, who experienced failures in vaccine coverage from 1992 to 1998 during the Federation of Bosnia and Herzegovina war and post-war period 26 , 36 . In Italy, approximately 90% of emergent measles cases were related to non-immunized children.…”
Section: Long-term Problems Of the Anti-vaccination Movementsmentioning
confidence: 99%
“…More girls than boys also acquired human herpesvirus (HHV-6), the pathogen of exanthema subitum (ES), in childhood; the acquisition of the virus was associated with female sex with the adjusted hazard ratio of 1.7 (95%CI 1.2-2.4) [4]. By contrast, more males contracted mumps in a large outbreak in Bosnia and Herzegovina in 2010-2011, a pattern which was also seen in the 2010 outbreak of rubella in Bosnia and Herzegovina [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study reported that boys were more likely to be infected with adenovirus than girls, but no age-specific incidences were given by sex [14]. Reports by Zerr et al [4] and Hukic et al [5] described differences in morbidity for HHV-6 and mumps infections between the sexes, but did not mention age-specificity at all. In an analysis of serological surveys of the age-specific distribution of antibody to parvovirus B19, the pathogen of EI, no sex-related difference was described [15].…”
Section: Introductionmentioning
confidence: 99%